103k views
3 votes
(7z^3+42z^2-15z+1)- (36z^2+12z-21)​

2 Answers

1 vote

Answer:

7z³ + 6z² - 27z + 22

Explanation:

It is given an expression in variable z,

(7z³ + 42z² - 15z + 1) - (36z² + 12z - 21)​

To find the simplified form

(7z³ + 42z² - 15z + 1) - (36z² + 12z - 21)​

= (7z³ + 42z² - 15z + 1 - 36z² - 12z + 21)​

= 7z³ + 42z² - 36z² - 15z -12z + 1 + 21

= 7z³ + 6z² - 27z + 22

Therefore the simplified expression is = 7z³ + 6z² - 27z + 22

User Eric Schweichler
by
5.0k points
1 vote

Answer:

7z^3+6z^2-27z+22

Explanation:

The given question is of subtraction:

So,

(7z^3+42z^2-15z+1)- (36z^2+12z-21)​

=7z^3+42z^2-15z+1-36z^2-12z+21

Combining alike terms to simplify

=​7z^3+42z^2-36z^2-15z-12z+1+21

=7z^3+6z^2-27z+22

So the answer in simplified form is:

7z^3+6z^2-27z+22 ..

User Yanko
by
5.5k points